Does suppression of oscillatory synchronisation mediate some of the therapeutic effects of DBS in patients with Parkinson's disease? - Eusebio, Alexandre; Cagnan, Hayriye; Brown, Peter (Frontiers in Integrative Neuroscience, 2012)
There is growing evidence for exaggerated oscillatory neuronal synchronisation in patients with Parkinson’s disease. In particular, oscillations at around 20 Hz, in the so-called beta frequency band, relate to the cardinal symptoms of bradykinesia and rigidity. Deep brain stimulation of the subthalamic nucleus can significantly improve these motor impairments. Recent evidence has demonstrated reduction of beta oscillations concurrent with alleviation of PD motor symptoms, raising the possibility that suppression of aberrant activity may mediate the effects of DBS. Here we review the evidence supporting suppression of pathological oscillations during stimulation and discuss how this might underlie the efficacy of DBS. We also consider how beta activity may provide a feedback signal suitable for next generation closed loop and intelligent stimulators.